To rewrite the equation \( \frac{4x}{3x - 12} + 3 = 10 \) in the form of two equations joined by "and," we can first isolate the fraction.
Starting from the original equation:
-
Subtract 3 from both sides:
\[ \frac{4x}{3x - 12} = 10 - 3 \]
This simplifies to:
\[ \frac{4x}{3x - 12} = 7 \]
-
Now, we can separate the equation into two parts. We can express it as:
\[ 4x = 7(3x - 12) \quad \text{and} \quad 3x - 12 \neq 0 \]
So, the final form is:
\[ 4x = 7(3x - 12) \quad \text{and} \quad 3x - 12 \neq 0 \]